Incoherent population mixing contributions to phase-modulation two-dimensional coherent excitation spectra - Grégoire, Pascal; Ajay Ram Srimath Kandada; Vella, Eleonora; Leonelli, Richard; Silva, Carlos (arXiv.org, 2017)
We present theoretical and experimental results showing the effects of incoherent population mixing on two-dimensional (2D) coherent excitation spectra that are measured via a time-integrated population and phase-sensitive detection. The technique uses four collinear ultrashort pulses and phase modulation to acquire two-dimensional spectra by isolating specific nonlinear contributions to the photoluminescence or photocurrent excitation signal. We demonstrate that an incoherent contribution to the measured lineshape, arising from nonlinear population dynamics over the entire photoexcitation lifetime, generates a similar lineshape to the expected 2D coherent spectra in condensed-phase systems. In those systems, photoexcitations are mobile such that inter-particle interactions are important on any timescale, including those long compared to the 2D coherent experiment. Measurements on a semicrystalline polymeric semiconductor film at low temperature show that, in some conditions in which multi-exciton interactions are suppressed, the technique predominantly detects coherent signal and can be used, in our example, to extract homogeneous linewidths. The same method used on a lead-halide perovskite photovoltaic cell shows that incoherent population mixing of mobile photocarriers can dominate the measured signal since carrier-carrier bimolecular scattering is active even at low excitation densities, which hides the coherent contribution to the spectral lineshape.